If it's not what You are looking for type in the equation solver your own equation and let us solve it.
180=7x-3(-6x+11)
We move all terms to the left:
180-(7x-3(-6x+11))=0
We calculate terms in parentheses: -(7x-3(-6x+11)), so:We get rid of parentheses
7x-3(-6x+11)
We multiply parentheses
7x+18x-33
We add all the numbers together, and all the variables
25x-33
Back to the equation:
-(25x-33)
-25x+33+180=0
We add all the numbers together, and all the variables
-25x+213=0
We move all terms containing x to the left, all other terms to the right
-25x=-213
x=-213/-25
x=8+13/25
| q/14+15=16 | | 7(-10-2x)=-238 | | v-2/5=-9 | | 3(q+1)=12 | | 2.2t-3=-31.2 | | -2(v)=9=25 | | 15-2y=7y | | b+5/17=-1 | | 42+9y+4=-10 | | 103+42+x=180 | | d/2+9=10 | | 4x-2-7x=119 | | 11=18+8f | | 65+x+x=128 | | 10(b+2)=20 | | 109+42+x=180 | | q/9+5=10 | | 10x+5-2x=3x+25 | | 4=t/2.5 | | 4u+19=-1 | | 6-5y=3y-2 | | 8(-2x-4)+13=52 | | t/19+9=14 | | -(x-5)-2x=4 | | 8x+3x-243=76 | | c+14/3=14 | | 5(2q-8)=10 | | 4-7(1-8c)=-20 | | 4x+2=8-10 | | x+59+121=180 | | 6x-109-11x=66 | | 10x+85=180 |